K-Alpha Calculator–Krippendorff's Alpha Calculator: A user-friendly tool for computing Krippendorff's Alpha inter-rater reliability coefficient - Marzi, Giacomo; Balzano, Marco; Marchiori, Davide (MethodsX, 2024)
Krippendorff's Alpha is a measure for assessing inter-rater reliability, facilitating triangulated evaluations among multiple raters. Indeed, Krippendorff's Alpha is key in validating the dependability of human assessments, thereby reinforcing the robustness of human-based choices in contexts where interpretive variability could otherwise undermine the research outcomes. Despite its versatility across various data types, the procedure for computing this coefficient might limit its applicability for researchers unfamiliar with specialised statistical software. Addressing this issue, this paper introduces the “K-Alpha Calculator”—Krippendorff's Alpha Calculator—a freely accessible, user-friendly, web application available at https://www.k-alpha.org designed for easy computation of Krippendorff's Alpha. By offering a web interface without any software dependency, the K-Alpha Calculator seeks to promote the broader integration of such a reliability metric in research processes. We envisage that the tool's contribution could support researchers in enhancing methodological rigour, fostering conclusions are rooted in triangulated interpretations and assessments. The K-Alpha Calculator is both a computational tool and an educational resource, encouraging more researchers to include reliability measures in their studies.•Development of the K-Alpha Calculator.The study centres on the introduction of a web-based application: the K-Alpha Calculator. The tool is developed to simplify the calculation of Krippendorff's Alpha without any required software dependency.•User-friendly interface for diverse data types.The K-Alpha Calculator is characterised by its accessibility and user-friendliness, designed to simplify the procedures for computing the Krippendorff's Alpha. Its utility extends to various data types, which aligns with the intrinsic versatility of this coefficient. [Display omitted]